The physiological overload of handball: a study about blood lactate and heart rate in trained and untrained subjects - Thaís Guimarães Eleno; Eduardo Kokubun (Journal of Physical Education (Maringá), 2008)
Collective sports which involve ball handling, such as handball, present alternate high and low intensity activities due to changes in velocity and direction of displacement and ball handling, modifying heart and blood lactate. 8 trained and 9 untrained male participants were submitted to 15 trials of 30 meters running tests in 9, 8 and 7 seconds, with 25 seconds rest between each trial and one minute rest between courses. Once the objectives of present study were to assess the physiological responses to the handball dribbling and their relations to the skill level of the subjects, this procedure was applied with and without handball dribbling, and blood lactate and heart rate were obtained in all test conditions. Sprint times were near that suggested one and they did not suffer any effect of dribbling or skill level. The main results of that rate and blood lactate were: 142, 156 and 177 of HR and 0.84, 1.11 and 2.82 of BL for the “without ball” condition in trained participants for 9, 8 and 7s respectively. To the “with ball”condition the same individuals presented 143, 158 and 176 of HR and 0.83, 1.21 and 2.66 of BL for 9, 8 and 7s respectively. The untrained participants presented for the “without ball” condition, 137, 151 and 170 of HR and 1.51, 1.66 and 3.4 of BL for 9, 8 and 7s respectively. And to the “with ball” condition the results were 138, 153 and 173 of HR and 1.12, 1.6 and 2.87 of BL for 9,8 e 7s respectively. The heart rate and blood lactate increased as the exercise intensity rose, but the dribbling and skill level have not influenced these variables. These results suggest that: a) handball dribbling is not an additional physiological overload to the players; b) individuals’ skill level is not relevant to the analyzed variables.